Hybrid subjectivities Intercultural communication, immigration and gender in Spain - Vañó Juárez, Paola (2013)
The following essay focuses on the problem of immigrant woman, particularly woman from Latin America, who feels the subjective bonds with Spanish culture, the one who contributes with her work to the community where she is inserted. The women’s situation leaving her home country looking for welfare and a change in her lifestyle is analyzed. However, when she reached her goal, she finds herself facing a triple discrimination: social, gender and ethnic one. This situation is reflected in television and advertising which transmit stereotypes and prejudices from these social minorities, in other cases the mass offers turn them invisible as if they were not inserted in society. It is expected a change in mass media playing akey role in terms of equity in favor of immigrant women, emphasizing educational programs in order to improve substantially the situation of immigrant woman.